Hawker Fare : stories & recipes from a refugee chef's Isan Thai & Lao roots - Syhabout, James; Birdsall, John (Ecco, an imprint of HarperCollins Publishers, 2018)
"From chef James Syhabout of two-Michelin-star restaurant Commis, an Asian-American cookbook like no other--simple recipes for cooking home-style Thai and Lao dishes"--